Reduced extracellular space in the brain of tenascin-R- and HNK-1-sulphotransferase deficient mice - Syková, Eva; Vorísek, Ivan; Mazel, Tomás; Antonova, Tatiana; Schachner, Melitta (The European journal of neuroscience, 2005)
Tenascin-R (TN-R), a large extracellular glycoprotein, is an important component of the adult brain's extracellular matrix (ECM); tenascin-C (TN-C) is expressed mainly during early development, while human natural killer 1 (HNK-1) is a sulphated carbohydrate epitope that attaches to these molecules, modifying their adhesive properties. To assess their influence on extracellular space (ECS) volume and geometry, we used the real-time iontophoretic method to measure ECS volume fraction alpha and tortuosity lambda, and diffusion-weighted magnetic resonance imaging (MRI) to measure the apparent diffusion coefficient of water (ADC(W)). Measurements were performed in vivo in the cortex and CA1 hippocampal region of TN-R-, TN-C- and HNK-1 sulphotransferase (ST)-deficient adult mice and their wild-type littermate controls. In both cortex and hippocampus, the lack of TN-R or HNK-1 sulphotransferase resulted in a significant decrease in alpha and lambda. Compared with controls, alpha in TN-R-/- and ST-/- mice decreased by 22-26% and 9-15%, respectively. MRI measurements revealed a decreased ADC(W) in the cortex, hippocampus and thalamus. ADC(W) reflected the changes in alpha; the decrease in lambda indicated fewer diffusion obstacles in the ECS, presumably due to a decreased macromolecular content. No significant changes were found in TN-C-/- animals. We conclude that in TN-R-/- and ST-/- mice, which show morphological, electrophysiological and behavioural abnormalities, the ECS is reduced and its geometry altered. TN-R, as an important component of the ECM, appears to maintain an optimal distance between cells. The altered diffusion of neuroactive substances in the brain will inevitably affect extrasynaptic transmission, neuron-glia interactions and synaptic efficacy.
Keywords: Animals; extracelulární prostor; Female; Iontophoresis; ženské pohlaví; Mice, Knockout; Extracellular Space; myši knockoutované; Quaternary Ammonium Compounds; Sulfotransferases; difuzní magnetická rezonance; Mice; kvartérní amoniové sloučeniny; mozek; myši; iontoforéza; Tenascin; počítačové zpracování obrazu; Brain; Diffusion Magnetic Resonance Imaging; tenascin; sulfotransferasy; zvířata; Mice, Inbred C57BL; Image Processing, Computer-Assisted; myši inbrední C57BL